Making healthy food choices : Food for sports - Morris, Neil. (London : heinemann, 2006)
Discusses the importance of making healthy food choices, focusing on the dietary needs af athletes, discussing carbohydrates, protein, fats, vitamins and minerals, fluids, training and competing, and related topics, and including a selection of recipes.
Keywords: Nutrition; Sports -- Physiological aspects